Transformation of the foreign language training system for the armed forces of Ukraine as a strategic factor in strengthening defense cooperation with NATO countries in the context of a potential peacekeeping mission in Ukraine - Semenenko, Oleh; Gurkovskyi, Volodymyr; Semenenko, Lilia; Romashyna, Zoriana; Yarmolchyk, Mariia; Moroz, Ihor (Social Development and Security, 2025)
Purpose:: to consider the current state and trends in the development of the system of foreign language training for servicemen of the Armed Forces of Ukraine, to analyze the experience of foreign language training in NATO countries and to develop substantiated proposals for improving the foreign language training of servicemen of the Armed Forces of Ukraine to increase their interoperability with the military structures of NATO countries, in particular in the context of a possible peacekeeping mission. Method: The work is based on the analysis of normative legal acts of Ukraine, strategic documents of the Ministry of Defense of Ukraine, NATO methods, scientific publications and international experience of language training of military personnel. Comparative analysis, systematic approach and generalization of empirical data are used. Findings: The necessity of optimizing the terms and intensity of foreign language training, changing the rules for selecting military personnel for language courses, introducing modern educational technologies and adapting training methods to NATO military standards is substantiated. Practical recommendations on the modernization of language training in the Armed Forces are offered. Theoretical implications: The article expands scientific ideas about reforming military education in the context of Ukraine’s integration into the Euro-Atlantic space. The proposed approaches can be used to improve state policy in the field of military language training and curriculum development.